2010
DOI: 10.1037/a0021779
|View full text |Cite
|
Sign up to set email alerts
|

Coping mediates the relationship between posttraumatic stress disorder (PTSD) symptoms and alcohol use in homeless, ethnically diverse women: A preliminary study.

Abstract: Homeless women are at increased risk for problematic alcohol use and posttraumatic stress disorder (PTSD). While coping motives have been shown to mediate the relationship between PTSD symptoms and alcohol problems in victims of sexual assault and domestic violence, it is unknown whether this relationship is evident in other trauma-exposed populations. The focus of this study was to examine whether drinking to cope mediated the relationship between PTSD symptoms and current alcohol use in a group of homeless, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 24 publications
(31 reference statements)
2
42
1
1
Order By: Relevance
“…In another college sample, Read et al found posttraumatic stress to be prospectively related to poorer coping over time [104]. Although coping did not mediate PTS-alcohol associations in this study, several other studies have found at least partial support for a meditational role of coping [99101]. In addition to coping skills themselves, the motivation to drink in order to cope—specifically with PTS—may also be an important factor to consider [9, 102, 103].…”
Section: Behaviorscontrasting
confidence: 44%
“…In another college sample, Read et al found posttraumatic stress to be prospectively related to poorer coping over time [104]. Although coping did not mediate PTS-alcohol associations in this study, several other studies have found at least partial support for a meditational role of coping [99101]. In addition to coping skills themselves, the motivation to drink in order to cope—specifically with PTS—may also be an important factor to consider [9, 102, 103].…”
Section: Behaviorscontrasting
confidence: 44%
“…Drinking with the motive to alleviate emotional distress or regulate negative affect (i.e., drinking to cope) has been consistently positively associated with PTSD symptoms. For instance, drinking to cope is associated with PTSD symptom levels among adults in clinical settings (Lehavot et al, 2013), adolescents (Dixon, Leen-Feldner, Ham, Feldner, & Lewis, 2009), female victims of domestic violence (Kaysen et al, 2007), survivors of sexual assault (Ullman, Townsend, Starzynski, & Long, 2006), women who are homeless (Yeater, Austin, Green, & Smith, 2010), and individuals with serious mental illness (O'Hare, Shen, & Sherrer, 2010). Furthermore, drinking to cope plays a greater role in mediating PTSD symptoms and alcohol consumption than more socially oriented drinking (O'Hare & Sherrer, 2011).…”
Section: Trauma Avoidance and Alcohol Use Motivesmentioning
confidence: 95%
“…As noted, consequences from drinking may compromise coping resources, resulting in poorer post-trauma adaptation and greater PTSD symptoms. Though some studies have examined coping as a mediator of PTSD on drinking outcomes (Veenstra et al, 2007; Yeater et al, 2010), there have been no prospective tests of coping as a mediator of the reverse pathway, whereby alcohol influences PTSD outcomes.…”
Section: Introductionmentioning
confidence: 99%